Experimental Study on the Photocatalytic Reduction of CO2 by Fe2O3/BiOIO3 Composite Photocatalyst. Issue 1 (May 2021) - Zou, Jianshu; Wu, Jiang
Abstract: Photocatalytic reduction of CO2 to produce renewable hydrocarbon fuels is of great significance for solving the greenhouse effect and energy crisis. However, due to some shortcomings of the photocatalyst itself, further research is needed to realize its industrial application. In this article, we prepared Fe2 O3 /BiOIO3 composite photocatalyst by a simple one-step hydrothermal method, and discussed the photocatalytic activity and reaction mechanism of Fe2 O3 /BiOIO3 composite photocatalyst through a series of characterization and photocatalytic reduction experiments. The band gap energy of the composite photocatalyst (2.32 ev) is smaller than that of pure BiOIO3 (2.98 ev), so the composite photocatalyst can absorb visible light. Since the edge of the conduction band of BiOIO3 is more positive than the edge of the Fe2 O3 conduction band, the photogenerated electrons in the Fe2 O3 conduction band can be transferred to the BiOIO3 conduction band, which makes BiOIO3 more reducible and can reduce CO2 to CO. This study can provide some reference for the field of photocatalytic reduction of carbon dioxide.